Overview of the Quality of Health Services Based on Expectations and Satisfaction From the Perspective of BPJS Nondinas Patients in Hospitals Using the Servqual Method - Ali Taufan; Rizki J W (Jurnal EduHealth, 2025)
This study targeted non-service BPJS patients for several reasons. First, it targeted BPJS patients based on the potential for service improvement. BPJS patients reported lower satisfaction than non-BPJS patients. This will provide valuable input for hospital management and other hospitals to improve overall service quality. Second, it targeted non-service patients because there has been no research examining the quality of healthcare services in this group. Service quality, consisting of tangibles, reliability, responsiveness, assurance, and empathy, was overall considered very satisfying by patients. The results of the service importance assessment, consisting of tangibles, reliability, responsiveness, assurance, and empathy, were overall considered very important by patients. A comparison between reality and expectations yielded an average gap score across all assessment aspects, such as tangibles, responsiveness, reliability, empathy, and assurance.